2010
DOI: 10.1097/ftd.0b013e3181fc8fbb
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Limited Sampling Strategies for Mycophenolic Acid After Mycophenolate Mofetil Intake in Adult Kidney Transplant Recipients

Abstract: Multiple limited sampling strategies (LSSs) have been proposed for estimation of mycophenolic acid (MPA) area under the concentration-time curve from 0 to 12 hours postdose (AUC 0-12) after mycophenolate mofetil intake. The aim of this study was to provide summary information on all published LSSs for MPA and to evaluate their predictive performance in an independent population of kidney transplant recipients. Seventy-eight LSSs for MPA were identified. Sixty-nine full AUC profiles were collected from 45 subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 52 publications
0
27
0
Order By: Relevance
“…Not achieving an adequate AUC 0-12h may have important implications for therapeutic efficacy 12 ; consequently, LSS are recommended because MPA predose concentrations are only weakly correlated with AUC 0-12h . [18][19][20][21][22][23] Limited sampling for 2-3 hours after MMF can lead to an acceptable estimation of MPA AUC 0-12h , and different algorithms have been published. [18][19][20][21][22][23] However, these LSS cannot be used for EC-MPS, because delivery of MPA with this formulation in the intestine is more variable than delivery of MMF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not achieving an adequate AUC 0-12h may have important implications for therapeutic efficacy 12 ; consequently, LSS are recommended because MPA predose concentrations are only weakly correlated with AUC 0-12h . [18][19][20][21][22][23] Limited sampling for 2-3 hours after MMF can lead to an acceptable estimation of MPA AUC 0-12h , and different algorithms have been published. [18][19][20][21][22][23] However, these LSS cannot be used for EC-MPS, because delivery of MPA with this formulation in the intestine is more variable than delivery of MMF.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial research has been conducted to develop LSS to estimate MPA AUC 0-12h in solid organ recipients treated with MMF. [19][20][21][22] However, evidence in patients treated with EC-MPS is scant.…”
Section: Introductionmentioning
confidence: 98%
“…However, the limitation of these methods is that they are based on data collected bearing similar conditions. The generalizability and transferability of these developed LSS to another setting remains an open problem [9,16,18]. This is what we addressed in the current paper.…”
Section: Discussionmentioning
confidence: 64%
“…The predictive performance of LSS is generally evaluated through the calculation of their bias and precision [17]. Though these criteria inform a certain validity of the LSS, their predictive power and transferability should not be taken for granted when different patient subpopulations and contexts are involved [18]. This fact explains the variety of LSS reported for the same drug by different research groups [9,19].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, limited sampling strategies, where MPA exposure is estimated from a few samples, have shown good correlation with AUC 0-12h . 44,45 Recently, prospective, randomized, multicenter studies validating the benefit of TDM using LSS have been published. 35,36 The APOMYGERE trial, applying the population-based pharmacokinetic model and maximum a posteriori probability Bayesian methodology, found that the incidence of treatment failure was significantly lower in the concentration-controlled group.…”
Section: Therapeutic Drug Monitoringmentioning
confidence: 99%